Dinamika Tata Kelola Pertambangan: Studi Kasus Galian C di Desa Magagiri Kecamatan Bojonegara Kabupaten Serang - Siti Dinda Rahayu; Tri Nurul Aida; Adelia Rismayani; Wahyu Kartiko Utami (Journal of Creative Student Research, 2026)
Category C mining activities in Margagiri Village, Bojonegara District, Serang Regency provide economic benefits to local communities but also generate various environmental and social problems due to the suboptimal governance of natural resources. This study aims to analyze the governance dynamics of Category C mining using Elinor Ostrom’s Common-Pool Resources (CPR) theory. The research employed a qualitative method with a case study approach. Data were collected through in-depth interviews, field observations, documentation, and literature review. The findings indicate that mining governance has not been implemented optimally, as reflected in unresolved mining boundary issues, ineffective monitoring and supervision, limited community participation in decision-making processes, and weak coordination among stakeholders in natural resource management. These conditions have contributed to environmental degradation, an increased potential for social conflicts within the community, and the failure to achieve sustainable natural resource management. Therefore, strengthening the monitoring and supervision system, enhancing community participation, improving institutional coordination, and fostering a shared commitment among the government, mining operators, and local communities are essential to achieving sustainable, equitable mining governance that prioritizes environmental conservation and long-term community welfare.